Optimising the selection of candidates for neoadjuvant chemotherapy amongst patients with node‐positive penile squamous cell carcinoma. (1st April 2020) - Bandini, Marco; Albersen, Maarten; Chipollini, Juan; Pederzoli, Filippo; Zhu, Yao; Ye, Ding‐Wei; Ornellas, Antonio A.; Watkin, Nick; Ager, Michael; Hakenberg, Oliver W.; Heidenreich, Axel; Raggi, Daniele; et al.
Abstract : Objectives: To identify predictors of poor overall survival (OS) amongst patients with penile squamous cell carcinoma (pSCC) with clinical inguinal lymphadenopathy (cN+), in order to define the best candidates for neoadjuvant chemotherapy (NAC). Patients and Methods: Using an international, multicentre database of 924 patients with pSCC, we identified 334 men who harboured cN+ with available clinical and follow‐up data. Lymph node involvement was defined either by the presence of palpable inguinal node disease or by preoperative computed tomography (CT) assessment. Fluorine‐18 fluorodeoxyglucose positron‐emission tomography ( 18 F‐FDG‐PET)/CT scan was performed based on clinical judgment of the treating physician. Regression‐tree analysis generated a risk stratification tool for prediction of 24‐month overall mortality (OM). Kaplan–Meier explored the OS benefit related to the use of NAC according to the regression‐tree‐stratified subgroups. Results: Overall, 120 (35.9%), 152 (45.5%), and 62 (18.6%) patients harboured cN1, cN2, and cN3 disease. 18 F‐FDG‐PET/CT was performed in 48 (14.4%) patients, and 16 (4.8%) had inguinal and pelvic nodal PET detection. The median OS was 107 months, with a 24‐month OS of 66%. At regression‐tree analysis (area under the curve = 70%), patients with cN3 and cN2 with PET/CT‐detected inguinal and pelvic nodal activity had a higher risk of 24‐month OM (>50%). NAC was associated with improved 24‐month OS rates (54% vs 33%) only in this subgroup of patients ( P  = 0.002), which was also confirmed after multivariable adjustment (hazard ratio 0.28, 95% confidence interval 0.13–0.62; P  = 0.002). Conclusion: Patients with pSCC with cN3 or cN2 and inguinal and pelvic 18F‐FDG‐PET/CT scan detected disease had higher 24‐month OM rates according to our regression‐tree model. NAC was associated with improved OS only in these subgroups of patients. Our novel decision model may help to stratify cN+ patients, and identify those who most likely will benefit from NAC prior to radical surgical resection.